Part-Load Simulation and Energy Recovery Evaluation of an Electrically Turbocharged Engine Low Engine Speeds - Subramaniam, K.; Wan Salim, W.S-I. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Hybridization has become a crucial part of engine development for automotive manufacturers nowadays to produce efficient engines and electric turbochargers have become the center-piece of that development to cut carbon emissions. In this paper, we simulate an electrically turbocharged engine under part-load using a 1-D engine simulation software to estimate the amount of energy that can be recovered at different engine loads in a typical passenger vehicle. A conventional turbocharged engine and an electric turbocharged engine are first simulated under steady part load conditions with fixed target Brake Torque (Nm). Then the electric turbocharged engine is simulated to run at points between 1,000-2,000 rpm engine range to determine the amount of power recovered at low engine speed. From this study, the BSFC increases by 1.3% at 50% engine load at 4,000 rpm in the electrically turbocharged engine over conventional turbocharged engine whereas at 5,000 rpm it decreases by 2.4% at 75% engine load. A maximum of 3.22 kW was able to be recovered at 5,000 rpm 50% load and 1.5kW at low engine speeds.